EXTENT AND INTENSITY OF RURAL INDEBTEDNESS IN WARANGAL (RURAL) DISTRICT OF TELANGANA STATE: INSIGHTS FROM A FIELD STUDY - T. LAVANYA; ALDAS JANAIAH, CH. SHOURI KIRAN (The Journal of Research, PJTSAU, 2022)
The rural sector plays an important role in the Telangana economy. Nearly two-thirds of the Telangana population lives in rural areas, whose primary occupation is agriculture and allied sectors. The rural sector however is facing serious challenges such as increasing agrarian distress, rural and urban migration, shrinking non-farm employment, etc. As a result, rural distress is becoming a great challenge for future Telangana. Poverty is perhaps a major cause of rural indebtedness. The low level of rural incomes, the uncertain and primitive farming of small landholdings, make it impossible to meet the needs required for their living. It is reported that about 70 percent of India’s 90 million farmers spend more than they earn on average each month (Saha, 2017). Similarly, in Telangana state about 84 per cent of farm households spend more than their monthly income (NSSO, 2013). Often, rural people borrow to bridge this gap between meeting their farm and non-farm needs.